2010
DOI: 10.1111/j.1749-818x.2010.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Media to Teach About Language

Abstract: The number of documentaries being made about language has recently increased. Many of these have tremendous value in informal educational settings, but using them in classroom contexts in the United States often proves somewhat tricky. There are concerns about curricular fit, educational goals, potentially incendiary portrayals of topics, etc. High‐stakes testing further reduces the likelihood that language‐related documentaries will be used in schools, especially among populations who may benefit most from ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Interestingly, the discussions in Module 4 focused on linguistic discrimination and power earned the highest average scores. PSTs found the video texts to be the most useful, a finding that aligns with earlier research on teaching about language variation (Reaser, 2010).…”
Section: Evaluation Of the Curriculumsupporting
confidence: 76%
“…Interestingly, the discussions in Module 4 focused on linguistic discrimination and power earned the highest average scores. PSTs found the video texts to be the most useful, a finding that aligns with earlier research on teaching about language variation (Reaser, 2010).…”
Section: Evaluation Of the Curriculumsupporting
confidence: 76%
“…Both authors (López, 2010;Peris, 2001) analyzed both perspectives from Spanish as a foreign language (SFL), not taking English as the foreign language studied, although these contributions can be considered valid to take them as an educational reference. Reaser (2010) affirmed the necessity to implement linguistic principles in the class using methods like the use of social sciences like sources that contextualize knowledge, taking journalism as a great sample of social science that can be applied for the learning of communication processes.…”
Section: What Benefits Offer the Use Of The Journalistic Style In The Educative Environment?mentioning
confidence: 99%
“…While I've found that it's easy enough to jump to the relevant moment in a longer clip, there is a lack of editorial control on the SA website, unless someone takes the time to download that content, edit it, re-upload it, and link to it themselves. Finally, there is sociolinguistic content not widely available online, including many excellent medialingual producdons (Reaser 2010), like the Do You Speak American? documentary.…”
mentioning
confidence: 99%
“…The SA website supports wbat we already do in the classroom to bring a diversity of examples to better connect our students with sociolinguistic concepts. Media alone does not teach about language diversity, but it can be an effective tool to enhance sociolinguistic goals both in the classroom (Reaser 2010) and out. With its capacity as a quick, easy, and widely accessible online database for a wide variety of current artifacts, the SA website bas the potential to become a central resource for sociolinguistic teachers, scholars, and students.…”
mentioning
confidence: 99%